Hubungan komunikasi interpersonal dengan kepuasan pernikahan pada suami istri yang berkarier - Rani Novita Wardani; Yudi Suharsono; Sofa Amalia (Fakultas Psikologi, 2019)
Marital satisfaction will be realized if there is good interpersonal communication between husband and wife. To realize good interpersonal communication, effective interpersonal communication skills are needed so that they can distance themselves from destructive situations that will cause dissatisfaction in marriage. This study aims to determine the relationship between interpersonal communication with the marital satisfaction of husband and wife who have a career with the type of correlational quantitative research. The subject of this study involved 124 people or 62 couples who both worked in Malang district using the snowball sampling technique. Data collection uses the marital satisfaction scale and interpersonal communication scale, then analyzed using Pearson product moment correlation using the SPSS application. Based on the results of the study, the value of the correlation (r) on the husband was 0.791 with a probability of 0.000 (p <0.05) while the correlation value (r) for the wife was 0.700 with a probability of 0.000 (p <0.05). This means that there is a positive and significant relationship between interpersonal communication and marital satisfaction on a career husband and wife.